2010
DOI: 10.1089/fpd.2010.0581
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Cefotaxime-M-Producing Escherichia coli Isolates in Poultry Farms, But Not Swine Farms, in China

Abstract: The objective of this study was to investigate the distribution of extended spectrum β-lactamase (ESBL)-producing Escherichia coli isolates in swine and poultry farms in China. Rectal or cloaca swabs of swine and chicken were collected from four province-level regions of China, and E. coli isolates were recovered and tested for antimicrobial susceptibility. The isolates producing ESBLs were further characterized by pulsed-field gel electrophoresis (PFGE) and sequence analysis of genes encoding β -lactamases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…The diverse CTX-M enzymes detected in our study confirmed that the globally prevalent CTX-M-14 (22,42) and CTX-M-15 (32,37) enzymes are quite common in China, as reported previously (46). CTX-M-22, CTX-M-27, and CTX-M-65 have been reported on relatively few occasions (46), but mainly from China, and all have previously been observed among food animals in China (23,25,39). Thus, the detection of these enzymes in our isolates may indicate that food animals are an important reservoir for cephalosporin-resistant E. coli in China.…”
Section: Discussionsupporting
confidence: 90%
“…The diverse CTX-M enzymes detected in our study confirmed that the globally prevalent CTX-M-14 (22,42) and CTX-M-15 (32,37) enzymes are quite common in China, as reported previously (46). CTX-M-22, CTX-M-27, and CTX-M-65 have been reported on relatively few occasions (46), but mainly from China, and all have previously been observed among food animals in China (23,25,39). Thus, the detection of these enzymes in our isolates may indicate that food animals are an important reservoir for cephalosporin-resistant E. coli in China.…”
Section: Discussionsupporting
confidence: 90%
“…The ESBLs detected in food-producing animals or food in other non-European countries were: China (CTX-M-3, -13, -14, -15, -22, -24, -55, -64, -65; SHV-2, -12; TEM-52), Japan (CTX-M-2 and -14), and Senegal (SHV-12) (Ben Slama et al, 2010;Cardinale et al, 2001;Doi et al, 2009;Duan et al, 2006;Jouini et al, 2007;Kojima et al, 2005;Li et al, 2010a;Li et al, 2010b;Lim et al, 2009;Matsumoto et al, 2007;Rayamajhi et al, 2008;Shiraki et al, 2004;Tian et al, 2008;Wittum et al, 2010). These data show that mainly in Asian countries a higher diversity of CTX-Mvariants was observed.…”
Section: Esbl-subtypes Detected In E Coli and Salmonella From Food-pmentioning
confidence: 99%
“…These data show that mainly in Asian countries a higher diversity of CTX-Mvariants was observed. The presence of CTX-M-15 in E. coli of healthy and sick poultry and pigs in China and Korea may reflect a different epidemiology of ESBLs in these countries (Li et al, 2010a;Li et al, 2010b;Lim et al, 2009;Tian et al, 2008).…”
Section: Esbl-subtypes Detected In E Coli and Salmonella From Food-pmentioning
confidence: 99%
“…CTX-M-55 first isolated from E. coli in Thailand [33] developed from one point mutation of CTX-M-15, leading to replacement of amino acid 80.In recent years, CTX-M-55 in E. coli was separated from food animals and pets in China [33][34][35][36][37], but was very rare in clinical isolates. Yu et al [10] first detected it in S. Typhimurium from the stool of a child in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Gallati et al [40] [42], Guangzhou [43], and Beijing [35] in China. The blaCTX-M-65 gene detected in our investigation was the first time this gene was isolated in Salmonella from infected humans.…”
Section: Discussionmentioning
confidence: 99%